Growth performance, ruminal volatile fatty acids, health status and profitability in calves fed with milk supplemented with probiotics - Mehmet KÜÇÜKOFLAZ; Veli ÖZBEK; Savaş SARIÖZKAN; Berrin KOCAOĞLU GÜÇLÜ; Kanber KARA (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
Th is study aimed to determine the eff ects of milk supplemented with diff erent amounts (10-15 mL/day) of probiotics (eff ective microorganism-EM) during the period until weaning (70 days) of the calves on the growth performance [live weight (LW), live weight gain (LWG), the feed conversion ratio (FCR), body measurements], rumen volatile fatty acids (VFA), health status and profitability. A total of 42 calves were divided into three groups as control and two treatment groups (EM10 and EM15) containing 14 calves in each with similar live weights (42±5 kg), ages (7±3 days), breeds (7 Holstein and 7 Simmental), and sex (7 female and 7 male). Th e control group had no supplement in the milk, whereas the calves in the treatment groups received 10 mL of EM per calf per day orally or 15 mL of EM with milk. According to the study results, using the 10 and 15 mL/day of EM in calves had no significant eff ect on the performance (LW, LWG, FC, body measurements), VFA, disease rates, and profitability (P>0.05). However, in the first 30 days of the study, the FCR of the EM10 group was positively aff ected compared to the control group (P<0.05). In conclusion, slightly better results were obtained in both treatment groups regarding body measurements, VFA, disease rates, treatment costs and profitability than the control group.